Kontribusi AbÅ« al-QÄsim al-ZahrÄwÄ« pada Ilmu Kedokteran - Khoirudin, Ahmad Rijal; Muhammad, Taqiyuddin; Nidzom, M. Faqih; Fadillah, Izzuddin Ahmad; Arsandi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The purpose of this reseach was to explain al-ZahrÄwÄ«'s contribution to medical science. The method used by researchers was descriptive qualitative method with content analysis technique and research library. As a result of the data analysis, the researchers concluded several important points related to al-ZahrÄwÄ«'s contribution in medical science namely, 1) al-ZahrÄwÄ« was a pioneer in the use of several modified surgical instruments from pre-Islamic civilizations, 2) al-ZahrÄwÄ« invented several models of internal organ surgery such as the urinary tract and respiratory cavities, and 3) al-ZahrÄwÄ« made an important contribution in the field of medicine (pharmaceutical) in postsurgery procedures.